Water Demand Estimation Until 2045 in the New Capital City of Indonesia", Kutai Kartanegara Regency - Ika Meicahayanti; Juli Nurdiana; Dwi Ermawati Rahayu; Alvi Rahmawati (Gema Lingkungan Kesehatan, 2025)
ABSTRACTThe National Capital (IKN) in East Kalimantan is a planned governmental center to achieve the "Golden Indonesia" vision by 2045. Kutai Kartanegara Regency serves as a partner to IKN, with parts of its territory designated as IKN development areas, including the sub-districts of Loa Janan, Loa Kulu, Sanga Sanga, Muara Jawa, West Samboja, and Samboja. This partnership impacts various needs in the area, including the demand for clean water. This study aims to estimate the clean water demand in these six sub-districts up to 2045. The analysis of clean water needs was conducted based on population projections using arithmetic, geometric, and least square methods. Water demand calculations were performed for average daily flow (Qrh), maximum daily flow (Qhm), and peak hourly flow (Qjp), with Qjp serving as the reference for meeting clean water needs. The findings indicate that water demand increases in line with population projections and is influenced by territorial changes and the area's development as part of IKN. In Loa Janan, Loa Kulu, and Sanga Sanga, where parts of the territory will become part of IKN, the water demand managed by the Kutai Kartanegara Regency Government is projected to decrease by 2045, from 400.7 L/s, 330.6 L/s, and 98.9 L/s to 106 L/s, 288.4 L/s, and 98.5 L/s, respectively. In contrast, the 2045 water demand for Muara Jawa, West Samboja, and Samboja is projected at 266.2 L/s, 175 L/s, and 222.9 L/s, respectively. The water demand in these three sub-districts must be met by the IKN authority as their entire areas fall within the IKN development region. A comprehensive analysis of water resources and the development of water supply infrastructure is needed to support clean water demands in the study area.